Synthesis of Zero-Valent Iron Nanoparticles for Ultrasonic Assisted Dye Removal: Modeling and Optimization - Amirasad Pourabadeh; Bentolhoda Mehdizadeh; Siroos Shojaei; Meysam Davoodabadi Farahani; Saeed Shojaei (Tehran University of Medical Sciences, 2022)
No Abstract